EMPLOYEE ENGAGEMENT DITINJAU DARI PERCEIVED ORGANIZATIONAL SUPPORT PADA KARYAWAN - Evelyn Nathalia; Tanisha Rajkaur; Raina Ananta Christien; Lycha Rosiani Br Sinulingga; Sri Hartini; Mukhaira El Akmal (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research was to analyze the association between employee engagement and perceived organizational support within the employee population. The study employed a purposive sampling method, involving a total of 99 participants as both the population and sample. Data collection was conducted using a Likert-type scale to measure participant responses. To analyze the data, both the Pearson Product-Moment Correlation and additional statistical techniques were utilized with the assistance of SPSS version 25.0 for Windows. The results of the hypothesis testing revealed a strong positive relationship exists between perceived organizational support and employee engagement, as indicated by the correlation coefficient (r = 0.815) and significance level (p = 0.000; p < 0.05). These findings suggest that an increase in employee engagement is generally associated with a higher perception of organizational support, and conversely, lower engagement tends to align with reduced perceived support.